Prognostic Potential of Secreted Modular Calcium-Binding Protein 1 in Low-Grade Glioma - Wang, Jing; Xia, Shu; Zhao, Jing; Gong, Chen; Xi, Qingsong; Sun, Wei (Frontiers in Molecular Biosciences, 2021)
Background: SMOC1 belongs to a family of matricellular proteins, it was involved in embryo development, endothelia cell proliferation, angiogenesis, integrin-matrix interactions, cell adhesion, and regulation of glucose metabolism. Previous studies showed that the expression of SMOC1 was increased in some tumors. However, the prognostic value and the biological function of SMOC1 in tumor remains unclear. Methods: In this study, we explored the expression profile and prognostic value of SMOC1 in pan-cancers, especially glioma via multiple databases, including Oncomine, GEPIA2, PrognoScan, Kaplan-Meier plotter and CGGA database. Furthermore, LinkedOmics was used to identify the genes co-expressed with SMOC1, and to perform Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways and Gene ontology (GO) analysis in low grade glioma (LGG). And CancerSEA database was used to evaluate the correlation between SMOC1 expression and functional state activities in glioma cells. In addition, TIMER and TISIDB database were used to evaluate the correlations between SMOC1 expression and tumor infiltrated immune cells in tumor microenvironment. Results: Compared with normal brain tissues, the expression of SMOC1 was increased in LGG tissues. The higher expression of SMOC1 was significantly correlated with better survival of LGG patients. Additionally, functional analyses showed that the SMOC1 co-expressed genes were inhibited in processes like response to type I interferon and interferon-gamma, lymphocyte mediated immunity, leukocyte migration, adaptive immune response, neutrophil mediated immunity, T cell activation and pathways including EMC-receptor interaction, Th17 cell differentiation, leukocyte trans-endothelial migration in LGG. Moreover, the expression of SMOC1 was correlated with stemness, hypoxia, EMT and metastasis of glioma cells. Additionally, the expression of SMOC1 expression was negatively correlated with levels of infiltrating B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils and dendritic cells and gene markers of most immune cells in LGG. Conclusions: Our results suggest that SMOC1 could be a potential biomarker to determine prognosis and might play a specific role in the tumor microenvironment of glioma, thereby influencing the development and progression of glioma. This findings provide some new insights for further investigation.